Covalent 2D Cr2Te3 ferromagnet - Mengying Bian; Aleksandr N. Kamenskii; Mengjiao Han; Wenjie Li; Sichen Wei; Xuezeng Tian; David B. Eason; Fan Sun; Keke He; Haolei Hui; Fei Yao; Renat Sabirianov; et al. (Materials Research Letters, 2021)
To broaden the scope of van der Waals 2D magnets, we report the synthesis and magnetism of covalent 2D magnetic Cr2Te3 with a thickness down to one-unit-cell. The 2D Cr2Te3 crystals exhibit robust ferromagnetism with a Curie temperature of 180 K, a large perpendicular anisotropy of 7 × 105 J m−3, and a high coercivity of ∼4.6 kG at 20 K. First principles calculations further show a transition from canted to collinear ferromagnetism, a transition from perpendicular to in-plane anisotropy, and emergent half-metallic behavior in atomically-thin Cr2Te3, suggesting its potential application for injecting carriers with high spin polarization into spintronic devices.